PENGEMBANGAN KAPASITAS ORGANISASI PELAYANAN SOSIAL BERBASIS KEAGAMAAN DI BAITULMAAL MUAMALAT BANDUNG - Haifa, Nisa; Huraerah, Abu (Jurnal Ilmiah Kebijakan dan Pelayanan Pekerjaan Sosial (Biyan), 2024)
This research examines faith-based services at Baitulmaal Muamalat Bandung to address its relationship with the development of faith-based organisations. Capacity building in social service organisations is an important part of fulfilling roles and goals to achieve a good level of quality in providing benefits to many people in accordance with Islamic law. The research method used is a qualitative method, in order to obtain an in-depth understanding of social phenomena in faith-based organisations, in relation to organisational development. So that the approach used is a case study of the Baitulmaal Muamalat Bandung institution, to explore the dynamics of development in it. To get informants who are relevant and have special characteristics for research purposes, the informant selection technique is purposive sampling by sorting out informants who are considered to have knowledge and experience in development work at Baitulmaal Muamalat Bandung. Based on this description, this research aims to analyse the capacity of religious-based social service organisations in Baitulmaal Muamalat Bandung, such as opportunities, strengths, and challenges faced. Then, it can identify the development of the capacity of religion-based organisations in Baitulmaal Muamalat Bandung. The results of the analysis found that Baitulmaal Muamalat Bandung was able to optimise organisational development through individual and collective cooperation in it. So that the social services provided are quality and effective, this cannot be separated from the success of processing the resources owned through the values and religious bases used in Baitulmaal Muamalat Bandung